Men in the age of (formal) equality: The curious case of Khamtokhu and Aksenchik - Novaković Milica (Anali Pravnog Fakulteta u Beogradu)
Equality before the criminal law and protection of persons with restricted personal liberty in the European states diverge. The European Court of Human Rights has been engaged in establishing and protecting standards and principles for fair pre-conviction proceedings. However, when it comes to sentencing, sex and gender equality, and non-discrimination in sentencing, the European Court faces its own limitations. It has established that there is no consensus in matters of (un)equal treatment of men and women in criminal sentencing in Europe, but has failed to address a more significant issue - is exemption of an entire sex justifiable and reasonable, even in the absence of the afore consensus at European level. This analysis attempts to answer the following questions that arose from this case: Does formal equality eliminate discrimination? When should formal equality yield to achieve genuine equality? Is gender equality attainable and how do we regulate it?